2019
DOI: 10.1590/1413-785220192703215572
|View full text |Cite
|
Sign up to set email alerts
|

Anterolateral Approaches for Proximal Humeral Osteosynthesis: A Systematic Review

Abstract: Objective: Anterolateral approaches for proximal humerus osteosynthesis have great advantages because they allow direct exposure of the lateral aspect of the humerus without the muscular retraction seen in the deltopectoral approach. However, much resistance is found among surgeons due to the potential risk of iatrogenic injury to the axillary nerve. To identify the incidence of axillary nerve iatrogenic lesions and evaluate the functional results of proximal humerus osteosynthesis with locking plates using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
1
8
0
3
Order By: Relevance
“…In this study, none of the patients in the DI group were found to have clinical neurological signs of axillary nerve injury. This was consistent with previous reports [7,8,19,20] . In our opinion, the DI is a modification of the DS by extending the skin incision further distally beyond the area of the axillary nerve, which is directly visualized and protected.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, none of the patients in the DI group were found to have clinical neurological signs of axillary nerve injury. This was consistent with previous reports [7,8,19,20] . In our opinion, the DI is a modification of the DS by extending the skin incision further distally beyond the area of the axillary nerve, which is directly visualized and protected.…”
Section: Discussionsupporting
confidence: 93%
“…This was consistent with previous reports. [ 7 , 8 , 19 , 20 ] In our opinion, the DI is a modification of the DS by extending the skin incision further distally beyond the area of the axillary nerve, which is directly visualized and protected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some surgeons advocate plate and screw fixation for split GT fracture, and biomechanical study reveals that locking plate fixation provides the strongest and stiffest biomechanical fixation for split type greater tuberosity fractures [ 36 , 37 ]. However, there remain concerns of more deltoid muscle dissection, axillary nerve injury [ 38 ], and subacromial impingement after osteosynthesis with plate and screws [ 39 ]. Previous studies have reported good functional recovery in treating isolated GT fractures with screw fixation [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%